On Viktor Shklovsky’s Penchant for Forms - Skibska, Anna Maria (Poznańskie Studia Slawistyczne, 2017)
In the article, I have decided to sketch a brief portrait of the most significant Russian formalist Viktor Shklovsky. In order to comment upon his contribution to the development of literary theory, I cast some light on his original term ostranenie (estrangement, defamiliarization), which allows the formalist to expose the essential features of writing based on unlimited changes of the plot: they always assume a participation of irony, parody, and reinvention in art. The listed devices determine the progress in literature, which makes use of the old conventions to create new ones what occurs in the course of transgressing consolidated forms and functions. What is more, the process of transgression (or – to be more precise – self-transgression) is manifested by a disruptive activity of irony at the same time collaborating with literary traditions and thwarting them with the force of the eternal, perpetual reinvention.